International bank lending: Water flowing uphill? - John Hawkins (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
International bank lending is a major component of capital flows between advanced and emerging economies. However, in recent years these flows have been going the wrong way, like water flowing uphill. Even four years after the Asian crisis, there is a net flow of funds from emerging economies to banks in advanced economies. This paper looks at this phenomenon, starting by setting out the relevant data, and then looking at factors influencing these flows. These include both cyclical influences (both `push' and `pull') and structural changes within the banking industry. There is some evidence that international lenders are now discriminating more between the various emerging econ omies.
Keywords: F3; N1; F4; 330; international bank lending; capital flow; Internationale Kreditvergabe; Schwellenländer